2009
DOI: 10.1590/s1516-35982009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de forragem durante a rebrotação de capim-xaraés submetido a três estratégias de desfolhação

Abstract: RESUMO -Objetivou-se comparar a dinâmica do acúmulo de forragem em pastos de capim-xaraés [Brachiaria brizantha (A. Rich.) Stapf. cv. Xaraés] submetidos a três estratégias de desfolhação intermitente, uma baseada no calendário (pastejo a cada 28 dias) e duas na interceptação luminosa (IL), aos 95 ou 100% de interceptação luminosa. A massa de forragem (MF) pré-pastejo foi maior na estratégia de desfolhação aos 100% de interceptação de luz. Os piquetes pastejados aos 95% de interceptação de luz e a cada 28 dias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
2
52

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 13 publications
3
47
2
52
Order By: Relevance
“…This trait was observed in grasses managed with 95% light interception (Table 10) and less-severe postgrazing height (15 cm). The defoliation strategy with 95% light interception resulted in significantly lower post-grazing forage mass because the higher defoliation frequency led to shorter intervals between grazing cycles (Pedreira et al, 2009). However, this condition was compensated by the greater number of grazing cycles occurring in sites managed with 95% light interception, probably resulting in production of younger forage with better nutritional value.…”
Section: Resultsmentioning
confidence: 99%
“…This trait was observed in grasses managed with 95% light interception (Table 10) and less-severe postgrazing height (15 cm). The defoliation strategy with 95% light interception resulted in significantly lower post-grazing forage mass because the higher defoliation frequency led to shorter intervals between grazing cycles (Pedreira et al, 2009). However, this condition was compensated by the greater number of grazing cycles occurring in sites managed with 95% light interception, probably resulting in production of younger forage with better nutritional value.…”
Section: Resultsmentioning
confidence: 99%
“…The variation of 0.64 Mg ha -1 observed for DM is higher than SS for the treatment with no manure application, which confirms the structural changes in Marandu grass due to the nutritional contribution from the soil with increasing doses of poultry manure. According to Pedreira et al (2009), reduction in the availability factors for pasture development increases the time necessary for the pasture to reach 95% LI, causing the accumulation of stems and senescence to increase in this competition for light.…”
Section: Resultsmentioning
confidence: 99%
“…According to Pedreira et al (2009), the best strategy for the defoliation of Xaraés grass is 95% of light interception with residual height of 0.15 m for leaf accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Pedreira et al (2009), in a study with Xaraés grass at a post-grazing height of 15 cm, observed that after the rest period of about 22 days (time for the sward intercept 95% of PAR), it also showed increased accumulation of dead material. The highest leaf senescence rate in pastures grazed at 98% of LI can be attributed to greater competition for light and hence to lower tissue replacement in these pastures.…”
Section: Sward Light Interception (%)mentioning
confidence: 97%